Dental arch relationships in non-syndromic unilateral cleft lip and palate (UCLP) children of Pakistan - Arshad, Anas Imran (2016)
Globally, one out of every 700 live-births are affected by cleft lip and palate (CLP). By occurrence rate, it is one of the most common congenital orofacial birth anomaly. Literature indicates that CLP has a multifactorial origin, but genetics and environmental factors play a vital role and have been extensively studied individually and in conjunction. A multidisciplinary involvement is absolute to successfully manage and treat CLP. Primary surgical repairs are required to restore function and structure. Numerous designs for repair of CLP have been devised and practiced but the superiority of outcome following a single surgery over the rest has not been established. It is necessary to assess the treatment outcomes of these primary surgical repairs under the influence of congenital and post-natal factors. Audit can be performed to assess their effect on growth along with association of these confounding factors. Dentoalveolar relationships have been extensively used to assess the treatment outcome. Many indices have been developed which are based on different planes of growth. There is a severe lack of any literature of the treatment outcome and the role of different protocols in Pakistani population. Present study aims to determine the distribution of favourable/unfavourable treatment outcome by using GOSLON Yardstick, Modified Huddart/Bodenham system (MHB), and EUROCRAN yardstick, and to evaluate the association of the congenital and post-natal treatment factors on the treatment outcome based on these indices. 101 model pairs of Pakistani children having total unilateral cleft lip and palate with a mean age of 8.05 ± 0.79 were assessed using GOSLON, MHB and EUROCRAN yardsticks. The mean score for GOSLON index is 3.04 ± 1.25.The mean score of EUROCRAN based on dental grading is 2.72 ± 0.76, whereas, based on the palatal surface morphology, the mean score is 2.20 ± 0.73. The mean score of MHB, based on 5 groups, is 2.85 ± 1.30. With the help of present established database, teams providing cleft care can improve and establish protocols based on recent advanced techniques. Mean GOSLON scores, of Pakistani population unravel an intermediate treatment outcome and are comparable with other Asian population studies like Malaysia and Japan. According to Modified Huddart/Bodenham scoring system, Pakistani patients have a fair to poor treatment outcome. The results were more sensitive considering transverse planar growth. According to EUROCRAN index, based on dental grading, Pakistani patients have a higher frequency of poor treatment outcome, which was worse in comparison to the European populations. Based on palatal surface morphology, Pakistani TUCLP patients have the worse outcome in comparison to previous studies.